The New Normal in Dentistry after COVID-19 Outbreak - Tirth, Amit; Tafadar, Md Nazamuddin; Telgi, Ravishankar Lingesha; Dr, Monika (Asian Journal of Medical Sciences, 2020)
The outbreak of SARS-COV2 responsible COVID-19 disease created a worldwide health emergency. After its first case was accounted for in 2019, 31st December by World Health Organization in Wuhan city of china, and afterward spreading in different nations, with India surpassing cases even the inception nation as on twentieth of May 2020. The WHO declared the disease as pandemic way back and countries over the world adopting lockdown and contact tracing to limit the contagion. The virus transmits person-to-person predominantlythrough respiratory routes through direct contact, droplets and possibly aerosols. Because of the unique nature of practice in dentistry, most procedure generate significant amount of aerosols and droplets, posing a possible risk of infection transmission. Understanding the concern of risk of transmission in dental practice, this literature is aimed to discuss the possible risk associated with practice and aim to raise awareness of the same with preventive measures especially after the lockdown end in day to day practice.